Social Deficits or Interactional Differences? Interrogating Perspectives on Social Functioning in Autism - Lin, Xiangting Bernice; Lim, Choon Guan; Lee, Tih-Shih (Frontiers in Psychiatry, 2022)
Social dysfunction is a key characteristic of autism. Determining and treating autism-related social deficits have been challenging. The medical model views interpersonal difficulties in autism as a localized set of deficits to be managed, whereas the neurodiversity movement calls for the accommodation of differences by the larger community. One common assumption underlying these perspectives is a misalignment in social behaviors between autistic individuals and neurotypicals. This paper reviews and interrogates current perspectives on social functioning in autism to uncover the intricacies of such a notion. Even though extant literature has alluded to a misalignment in social behaviors between autistic and neurotypical individuals, it is uncertain where this disparity lies. Implications for future research and practice are discussed.